DIPPR Project 801, full version : evaluated standard thermophysical property values (BYU DIPPR, Thermophysical Properties Laboratory, 2005)
Knovelized version of DIPPR Project 801 (Full Version) database presents this renowned source of evaluated standard thermophysical property values in Knovel's interactive format. Nineteen fully searchable and filterable interactive tables enhanced with the equation plotter applet for graphical representation of the data provide a convenient access to a wealth of physical, thermodynamic, and transport properties for industrially important chemicals used in chemical process and equipment design.